Life and Career Skills in Mathematics Learning for High School Students in Indonesia: The Perspectives of Teachers and Students - Miftah, Ramdani; Kurniawati, Lia; Herman, Tatang; Juandi, Dadang; Maulida, Aya Shofia (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractStudents need to possess the right life and career skills to face future challenges. Therefore, this study aims to determine the effect of mathematics teachers' life skills on high school students in Indonesia. Data were collected from 190 mathematics teachers and 627 high school students through questionnaires consisting of 15 and 45 statements, respectively. The data collected were analyzed using the Structural Equation Modeling (SEM) method and the Smart-PLS v.3.2.9 software. The results showed that both mathematics teachers (77.50%) and high school students (83%) had a good understanding of life and career skills. However, their life skills were rated low due to teachers' difficulty in translating life and career skills into planning and implementing mathematics learning. This means that the methods used by teachers do not explore students' potential. Furthermore, the correlation between indicators of student life skills was found to be in the medium and large categories, indicating a significant relationship between the indicators of student life skills.AbstrakPara Siswa perlu memiliki keterampilan hidup dan karier yang tepat untuk menghadapi tantangan masa depan. Oleh karena itu, penelitian ini bertujuan untuk menentukan pengaruh keterampilan hidup guru matematika terhadap siswa SMA di Indonesia. Data dikumpulkan dari 190 guru matematika dan 627 siswa SMA melalui kuesioner yang terdiri dari 15 dan 45 pernyataan, masing-masing. Data yang terkumpul dianalisis menggunakan metode Structural Equation Modeling (SEM) dan perangkat lunak Smart-PLS v.3.2.9. Hasil penelitian menunjukkan bahwa baik guru matematika (77,50%) maupun siswa SMA (83%) memiliki pemahaman yang baik tentang keterampilan hidup dan karier. Namun, keterampilan hidup mereka dinilai rendah karena kesulitan guru dalam menerjemahkan keterampilan hidup dan karier ke dalam perencanaan dan pelaksanaan pembelajaran matematika. Ini berarti metode yang digunakan oleh guru tidak mengeksplorasi potensi siswa. Selain itu, korelasi antara indikator keterampilan hidup siswa ditemukan berada dalam kategori sedang dan besar, menunjukkan hubungan yang signifikan antara indikator keterampilan hidup siswa.How to Cite : Miftah, R., Kurniawati, L., Herman,T., Juandi, D., Maulida, A. S. (2022). Life and Career Skills in Mathematics Learning for High School Students in Indonesia: The Perspectives of Teachers and Students. TARBIYA: Journal of Education in Muslim Society, 9(2), 135-148. doi:10.15408/tjems.v9i2.25660.